Disaster management: Experiences of pediatric surgeons - User, Idil Rana; Bakal, Ünal; Saraç, Mehmet; Özokutan, Bülent Hayri; Kazez, Ahmet (Logos Medical Publishing, 2017)
Aim: Nowadays, many people get injured or lose their lives because of accidents, wars or natural disasters. For this reason, importance of disaster medicine has increased. In this study, we aimed to transfer the experiences of pediatric surgeons gained from these events. Material and Methods: After the terrorist attacks in Elazi? and Gaziantep which occurred in August 2016, disaster management handling of emergency department encountered problems and their solutions were discussed in university hospitals of aforementioned cities. Results: Injured people with no identification, multiple number of multiple-trauma victim admission within a short time, referrals exceeding the capacities of emergency services, laboratories, blood banks, radiology departments were the common issues encountered in both incidents. Necessity of using human and material sources efficiently, avoidance of unneccesary work-up, balancing work load by applicating triage among injured, making necessary preparations in the emergency services before the casualties arrived to the hospital, continuation of health care services by scheduling shifts after the stabilization of the initial acute phase were the lessons taken from these experiences. Conclusion: Prearranged hospital disaster plan may reduce these possible problems to a minimum level. The fact that traumatic events that may injure or cause them to lose their lives essentially requires integration of disaster medicine into the education of pediatric surgery. © 2017 Cocuk Cerrahisi Dergisi. All rights reserved.
Afet yönetimi: Çocuk cerrahlarinin deneyimleri
Keywords: Blast injury; Child; Disaster medicine; Trauma